Pemanfaatan Big Data dan Teknik Data Scraping untuk Analisis Kepuasan Pengguna Aplikasi Tangerang Live Berdasarkan Ulasan Pengguna - Anugrah, Lalu Reza; Pandega, Laksmana Rajwa; Haiqal, Rif’at Dwiki; Munawwar, Rais Fakhri; Fahlevvi, Mohammad Rezza; Apriyansa, Ari (Universitas Pahlawan Tuanku Tambusai, 2025)
Digital transformation in government encourages the presence of public services based on digital applications to improve efficiency and accessibility of services. One of them is the Tangerang LIVE Application which is an integrated platform owned by the Tangerang City Government. This study aims to analyze user satisfaction with the application by utilizing Big Data and Data Scraping techniques. Data is taken automatically from user reviews on the Google Play Store and analyzed using the TextBlob-based sentiment analysis method. Based on the results of the analysis of 6,971 reviews, it is known that 91.2% of reviews are neutral, 8.0% are positive, and 0.8% are negative. These findings indicate that most users provide neutral input, questions, or reports, while the technical aspects of the application still need to be improved to maximize user satisfaction. This study provides a real contribution in showing the potential of Big Data as a tool for evaluating digital public services in real-time and massively.